Cost Analysis of Prabumulih Storage Facilities - Aldiansah, Erza; Aliludin, Arson (Journal of Business and Management, 2013)
Cost Analysis of Prabumulih Storage Facilities (a Division of PT. Emprawi) in 2010 and 2011 are: to identify direct costs, indirect costs and cost allocation Jakarta office, classify these costs into variable costs and fixed costs based on behavior of the respective cost. Identification and classification results are used to determine total margin, cost per unit and break-even point (BEP). Direct costs include employee labor, security police, electricity, field examination accommodation, storage maintenance, social contributions, office supplies, and depreciation of assets, while indirect costs include bank administration, bid bond, business licenses and permits. Direct costs and indirect costs plus Jakarta office allocation formed total cost amounting to Rp. 599 million for the year 2010, consisting of 30% variable costs and 70% fixed costs, while for the year 2011 total cost amounting to Rp. 1.150 million consisting of 40% variable costs and 60% fixed costs. This division rented storage space of 7.650 m2 which generated revenues of Rp. 246 million in 2010 with a negative margin of Rp 353 million. While in 2011 it rented 53.850 m2 that generated revenue of Rp. 1,740 million with a positive margin of Rp. 590 million. BEP in 2010 was 54.859 m2 with the actual rent of 7.650 m2 reflecting respectively 63% and 9% of the available capacity of 86.400 m2, while in 2011, BEP was 29.637 m2 with actual rents of 53.850 m2 reflecting 26% and 47% of available capacity of 115.200 m2. To facilitate the cost analysis, it is recommended that PT. Emprawi improves cost information system that enhances a proper cost identification and classification.Â Keywords: storage facilities, cost identification, cost classification, direct cost, indirect cost, variable cost, fixed cost, Jakarta office allocation and break even point (BEP), PT. Emprawi â€“ Prabumulih